Auditory neuroscience: Balancing excitation and inhibition during development. - King, A (2010)
Two recent studies have described how the coupling of excitatory and inhibitory inputs to neurons in the auditory cortex changes during development. This process is driven by experience and, once complete, may limit the plasticity of the cortex in later life.